Perlindungan Hukum Pencipta-Penampil dalam Royalti dan Lisensi Konser Komersial: Legal Protection of Creator-Performers in Commercial Concert Royalty and Licensing - Rendy Setyo Prakoso; Zaenal Arifin; Wijayono Hadi Sukrisno (Hukum dan Masyarakat Madani, 2026)
This study aims to analyze the legal framework governing licensing and royalty arrangements for songs created and performed by creator-performers in commercial concerts, as well as to examine the forms of legal protection afforded to creator-performers under Law Number 28 of 2014 concerning Copyright. The research is motivated by the increasing number of copyright disputes in commercial performances, which reveal normative ambiguities between the obligation to obtain direct authorization from creators and the royalty payment mechanism administered through Collective Management Organizations (CMOs). This study employs a normative legal research method using statutory and conceptual approaches through the analysis of legislation, legal doctrines, and contemporary practices within the Indonesian music industry. The findings demonstrate that the Copyright Law and Government Regulation Number 56 of 2021 have not explicitly differentiated the legal position of creator-performers from non-performing creators, thereby creating legal uncertainty in the practice of commercial concerts. The novelty of this research lies in its normative argument concerning the necessity of differentiated legal protection between creator-performers and non-performing creators based on their moral, artistic, and economic attachment to musical works. The theoretical contribution of this study strengthens the development of copyright law discourse based on the characteristics of creators within the modern music industry, while its practical contribution provides recommendations for regulatory reform concerning licensing mechanisms, royalty management, and the exclusive rights of creator-performers in order to establish greater legal certainty and more proportionate legal protection within Indonesia’s music industry.   Abstrak Penelitian ini bertujuan menganalisis pengaturan perizinan dan pembayaran royalti atas penggunaan lagu yang diciptakan sekaligus dibawakan oleh penampil dalam konser komersial serta mengkaji bentuk perlindungan hukum terhadap pencipta-penampil berdasarkan Undang-Undang Hak Cipta. Penelitian ini dilatarbelakangi oleh meningkatnya sengketa penggunaan lagu dalam pertunjukan komersial yang menunjukkan adanya ambiguitas norma antara kewajiban memperoleh izin langsung dari pencipta dan mekanisme pembayaran royalti melalui Lembaga Manajemen Kolektif (LMK). Penelitian menggunakan metode hukum normatif dengan pendekatan perundang-undangan dan konseptual melalui analisis terhadap peraturan perundang-undangan, doktrin, serta praktik hukum yang berkembang dalam industri musik Indonesia. Hasil penelitian menunjukkan bahwa pengaturan dalam Undang-Undang Hak Cipta dan Peraturan Pemerintah Nomor 56 Tahun 2021 belum secara tegas membedakan kedudukan pencipta lagu yang sekaligus merupakan penampil dengan pencipta non-penampil, sehingga menimbulkan ketidakpastian hukum dalam praktik konser komersial. Kebaruan (novelty) penelitian ini terletak pada pengembangan argumentasi normatif mengenai perlunya diferensiasi perlindungan hukum antara pencipta-penampil dan pencipta non-penampil berdasarkan keterikatan moral, artistik, dan ekonomi terhadap karya yang dipertunjukkan. Kontribusi penelitian ini secara teoretis memperkuat pengembangan kajian hukum hak cipta berbasis karakteristik subjek pencipta dalam industri musik modern, sedangkan secara praktis memberikan rekomendasi reformulasi regulasi mengenai mekanisme lisensi, royalti, dan hak eksklusif pencipta-penampil guna mewujudkan kepastian hukum dan perlindungan yang lebih proporsional dalam industri musik Indonesia.